The price of hedging credit risk - Rogač, Jure; Mlinarič, Franjo (Naše gospodarstvo/Our economy, 2014)
Hedging of credit risk in the times of economic crisis, when 2/3 of domestic enterprises are late in payments (many of them ends up in bankruptcy), is an important competitive advantage. Our study is focused on the entire life cycle of debt-credit relationship in order to identify the most effective forms of insurance, from a legal and financial perspective. Therefore, we paid special attention to the analysis of the legal basis, respect for the business and financial principles and the risk of making the rating information.